Growth and Forage Value of Two Forage Rice Cultivars According to Harvest Time in Reclaimed Land of South Korea - Yeongmi Jang; Khulan Sharavdorj; Priscilla Nadalin; Suhwan Lee; Jinwoong Cho (Agronomy, 2022)
This study compares the growth of two forage rice cultivars (Oryza sativa L.), Mogwoo and Mogyang, in Midwest reclaimed land (Seongmun Tide Embankment, Korea) for two years to find the most adaptable cultivars and the appropriate harvest time. In the case of high salinity soil, it was confirmed that the influence of precipitation was relatively high on soil condition and crop growth. In Mogyang, plant height and culm length tended to decrease slightly as the precipitation increased. As for the tiller number, Mogyang was higher than Mogwoo, but the leaf area was about 1.5 to 2 times higher in Mogwoo than in Mogyang. In addition, in both cultivars, dry weight increased rapidly during the dough stage, and Mogyang was 1538 and 1815 g/m2, respectively, while Mogwoo was 2090 and 2752 g/m2, which was significantly higher. Mogyang had a CP of 4.8%, a TDN and RFV of 59.4%, 94.0, respectively, and Mogwoo had a CP of 9.7%, a TDN and RFV of 60.1%, 103.8, respectively, resulting in Mogwoo having higher values, and in particular Mogwoo was found to have better forage quality in the milk stage than in the dough stage. In addition, in terms of soil and climate conditions in Midwest reclaimed land, it was confirmed that the Mogwoo variety was the most suitable compared to Mogyang, and dry weight was higher in the dough stage than in the milk stage, but it was concluded that high forage quality could be obtained by harvesting during the milk stage.